2018
DOI: 10.7717/peerj.4497
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of new-onset right bundle-branch block in acute myocardial infarction patients: a systematic review and meta-analysis

Abstract: BackgroundPatients with acute myocardial infarction (AMI) and bundle-branch block have poor prognoses. The new European Society of Cardiology guideline suggests a primary percutaneous coronary intervention strategy when persistent ischemic symptoms occur in patients with persistent ischemic symptoms and right bundle-branch block (RBBB), but the level of evidence is not high. In fact, the presence of RBBB may lead to the misdiagnosis of transmural ischemia and mask the early diagnosis of ST-elevation myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
1
25
0
3
Order By: Relevance
“…This has important implications in our population, with >50% of patients being STEMI and possibly inducing some referral bias for BBB patients that might explain this discrepancy. In a head-to-head comparison, in non-contemporaneous studies, BBB patients were older, with more comorbidities and heart failure, similar to more recent studies and also to our own results [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This has important implications in our population, with >50% of patients being STEMI and possibly inducing some referral bias for BBB patients that might explain this discrepancy. In a head-to-head comparison, in non-contemporaneous studies, BBB patients were older, with more comorbidities and heart failure, similar to more recent studies and also to our own results [ [6] , [7] , [8] , [9] , [10] , [11] , [12] ].…”
Section: Discussionsupporting
confidence: 91%
“…A large meta-analysis confirmed that RBBB patients had the highest mortality (in-hospital and long-term), but in this analysis there was considerable heterogeneity across included studies [ 11 ]. In more recent studies, mortality rates in this subgroup did not improve much, despite substantial improvements in treatment [ [10] , [11] , [12] ]. Studies that compared new/old or persistent/transient BBB, consistently showed that new and permanent BBB (particularly RBBB), was associated with the worst outcome [ 6 , 7 , 12 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations